2012
DOI: 10.1152/ajplung.00190.2011
|View full text |Cite
|
Sign up to set email alerts
|

Terminal sialic acids are an important determinant of pulmonary endothelial barrier integrity

Abstract: The surface of vascular endothelium bears a glycocalyx comprised, in part, of a complex mixture of oligosaccharide chains attached to cell-surface proteins and membrane lipids. Importantly, understanding of the structure and function of the endothelial glycocalyx is poorly understood. Preliminary studies have demonstrated structural differences in the glycocalyx of pulmonary artery endothelial cells compared with pulmonary microvascular endothelial cells. Herein we begin to probe in more detail structural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 32 publications
(36 reference statements)
0
52
0
Order By: Relevance
“…The ability of PECAM-1 to localize to, and concentrate at, cell-cell junctions, where it carries out this function, is completely dependent on its ability to form trans PECAM-1/PECAM-1 homophilic interactions, an adhesive property of the PECAM-1 extracellular domain that was first proposed more than 25 years ago (54), shown to be due to diffusion trapping of the receptor at cell-cell junctions 10 years later (9) and most recently found to support endothelial cell junctional integrity in a potentially regulatable manner (17,55). Interestingly, Cioffi et al (56) have shown recently that not only are sialic acids an important determinant of endothelial barrier integrity but that, although the arterial endothelium is likely to display both ␣2,3 and ␣2,6 sialic acid residues, the cell surface receptors of microvascular endothelial cells are primarily ␣2,3-sialylated. Taken together with the findings presented here that ␣2,3-linked sialic acid residues support, whereas ␣2,6 sialic acids inhibit, PECAM-1-mediated homophilic interactions, it is tempting to speculate that PECAM-1 might be a target for a novel mode of regulating endothelial cell permeability; namely, dynamic glycan modification.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PECAM-1 to localize to, and concentrate at, cell-cell junctions, where it carries out this function, is completely dependent on its ability to form trans PECAM-1/PECAM-1 homophilic interactions, an adhesive property of the PECAM-1 extracellular domain that was first proposed more than 25 years ago (54), shown to be due to diffusion trapping of the receptor at cell-cell junctions 10 years later (9) and most recently found to support endothelial cell junctional integrity in a potentially regulatable manner (17,55). Interestingly, Cioffi et al (56) have shown recently that not only are sialic acids an important determinant of endothelial barrier integrity but that, although the arterial endothelium is likely to display both ␣2,3 and ␣2,6 sialic acid residues, the cell surface receptors of microvascular endothelial cells are primarily ␣2,3-sialylated. Taken together with the findings presented here that ␣2,3-linked sialic acid residues support, whereas ␣2,6 sialic acids inhibit, PECAM-1-mediated homophilic interactions, it is tempting to speculate that PECAM-1 might be a target for a novel mode of regulating endothelial cell permeability; namely, dynamic glycan modification.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a murine ARDS model suggested that the glycocalyx-modulated neutrophil diapedesis via heparinase-mediated glycocalyx shedding and consequent exposure of neutrophil adhesion molecules,12 while in vitro human data proposed that the sialic acid component of the glycocalyx maintained barrier function via regulation of cell-matrix and cell-cell interactions 13. Despite these and other observations (reviewed in ref.…”
Section: Structure and Function Of The Pulmonary Endotheliummentioning
confidence: 99%
“…Sialic acids, typically present at the distal ends of carbohydrate chains, are negatively charged carbohydrates [28,30]. In addition, terminal sialic acids promote endothelial barrier integrity, so treatment of epithelial monolayers with C. perfringens sialidases may lead to barrier disruption and may increase access for C. perfringens so they can adhere [64]. Therefore, nonspecific effects of secreted NanI on both charge and epithelial barrier integrity could help to increase toxin binding and C. perfringens colonization.…”
Section: Possible Contributions Of Sialidases To C Perfringens Dimentioning
confidence: 99%
“…Therefore, nonspecific effects of secreted NanI on both charge and epithelial barrier integrity could help to increase toxin binding and C. perfringens colonization. A C. perfringens sialidase (not specified) has, in fact, been shown to affect barrier resistance in some, but not all, host cells [64]. However, for some cell lines, nonspecific effects do not appear to completely explain NanI enhancement of C. perfringens adherence.…”
Section: Possible Contributions Of Sialidases To C Perfringens Dimentioning
confidence: 99%